Hutchinson, Mildred (audio interview #3 of 3) - Hutchinson, Mildred (b. 10/17/1894 - d. 1/14/2000); Wayman, Phyllis, interviewer
INTERVIEW DESCRIPTION - This third interview with Mildred Hutchinson, like the previous two, is sometimes difficult to hear both because of her soft voice and the background noise heard on the second side of the recording (3b). 1976-07